2017
DOI: 10.1016/j.gendis.2017.10.004
|View full text |Cite|
|
Sign up to set email alerts
|

Sox9 augments BMP2-induced chondrogenic differentiation by downregulating Smad7 in mesenchymal stem cells (MSCs)

Abstract: Cartilage injuries caused by arthritis or trauma pose formidable challenges for effective clinical management due to the limited intrinsic proliferative capability of chondrocytes. Autologous stem cell-based therapies and transgene-enhanced cartilage tissue engineering may open new avenues for the treatment of cartilage injuries. Bone morphogenetic protein 2 (BMP2) induces effective chondrogenesis of mesenchymal stem cells (MSCs) and can thus be explored as a potential therapeutic agent for cartilage defect re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…www.ecmjournal.org Also, in the present study, the longest time point was day 14, whilst previous studies have shown formation of cartilage-like tissue from BMSCs (with or without a scaffold) after 4 weeks in culture (Meinel et al, 2004;Xue et al, 2012). Sox-9 expression is also of particular importance, as it has been shown to inhibit bone morphogenetic protein 2 (BMP-2)-induced expression of osteopontin, to enhance collagen type II expression in mesenchymal stem cells (Zhao et al, 2017) and chondrocytes (Bell et al, 1997;Zhao et al, 1997) and to play a pivotal role in chondrogenesis and chondrocyte differentiation (Akiyama et al, 2002;Bi et al, 1999;Ikegami et al, 2011). Further, forced ectopic Sox-9 expression in vitro (in mouse hypertrophic chondrocytes) and in vivo (in mice) results in downregulation of collagen type X (Leung et al, 2011), which, although its deposition was enhanced in the presence of MMC, was detected in smaller amounts than collagen type I and II.…”
Section: Discussionmentioning
confidence: 57%
“…www.ecmjournal.org Also, in the present study, the longest time point was day 14, whilst previous studies have shown formation of cartilage-like tissue from BMSCs (with or without a scaffold) after 4 weeks in culture (Meinel et al, 2004;Xue et al, 2012). Sox-9 expression is also of particular importance, as it has been shown to inhibit bone morphogenetic protein 2 (BMP-2)-induced expression of osteopontin, to enhance collagen type II expression in mesenchymal stem cells (Zhao et al, 2017) and chondrocytes (Bell et al, 1997;Zhao et al, 1997) and to play a pivotal role in chondrogenesis and chondrocyte differentiation (Akiyama et al, 2002;Bi et al, 1999;Ikegami et al, 2011). Further, forced ectopic Sox-9 expression in vitro (in mouse hypertrophic chondrocytes) and in vivo (in mice) results in downregulation of collagen type X (Leung et al, 2011), which, although its deposition was enhanced in the presence of MMC, was detected in smaller amounts than collagen type I and II.…”
Section: Discussionmentioning
confidence: 57%
“…Standard surgical procedures were performed during knee arthroplasty and specimen collection did not involve any clinical intervention. The collection of human specimens and animal experiments in the present study were approved by the Ethics Committee of the First Affiliated Hospital of chongqing Medical University (Permit number: 2015-316), under which the effect of Smad7 on chondrogenesis and endochondral ossification (25), osteocyte TGFβ-Smad4 on osteoblastic and osteoclastic differentiation (26) had been previously have identified. Written informed consent was obtained from participants.…”
Section: Methodsmentioning
confidence: 99%
“…The qPCR reactions were done in triplicate. All expression values were normalized to the reference gene GAPDH expression by using the 2 -ΔΔCt method [50][51][52][53]. The sequences of the qPCR primers are listed in Supplemental Table 1.…”
Section: Cell Transfectionmentioning
confidence: 99%